Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fresc.2021.709682
|View full text |Cite
|
Sign up to set email alerts
|

ICF Personal Factors Strengthen Commitment to Person-Centered Rehabilitation – A Scoping Review

Abstract: Background: The International Classification of Functioning, Disability and Health (ICF) classification is a biopsychosocial frame of reference that contributes to a holistic understanding of the functioning of a client and the factors involved. Personal factors (PFs) are not currently classified in the ICF due to large societal and cultural diversity and lack of clarity in the scope of such factors.Aims: To ascertain which factors in the ICF classification have been defined as PFs in different studies and wha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Some classification systems have been developed by others, such as those by Geyh et al (2019) and Grotkamp et al (2020). The Grotkamp classification system was selected for this Core Set development because they present a more comprehensive classification (Karhula et al, 2021). Relatedly, there may be ambiguity as to what constitutes a personal factor (Simeonsson et al, 2014), and there is overlap between those considered “personal” and those coded in the ICF (Grotkamp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some classification systems have been developed by others, such as those by Geyh et al (2019) and Grotkamp et al (2020). The Grotkamp classification system was selected for this Core Set development because they present a more comprehensive classification (Karhula et al, 2021). Relatedly, there may be ambiguity as to what constitutes a personal factor (Simeonsson et al, 2014), and there is overlap between those considered “personal” and those coded in the ICF (Grotkamp et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ICF seeks to address health and functioning as a relationship between health condition, body functions and structures, activities, participation, environmental factors and personal factors ( 2 ). The latter are not classified in the ICF coding system mainly due to ethical aspects related to such factors as well as challenges reaching common factors based on societal and cultural diversity ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the role of contextual factors often emphasizes the environmental factors component of context (12)(13)(14)(15)(16), rather than the personal factors component. However, some disability scholars have argued that personal factors are the greatest contributors to chronic illness and disability (17-19), as they can alter an individual's commitment to participation in rehabilitation and explicate an individual's hopes and desires that shape their experience (20). The recognition of the important role that personal factors play on a person's disability experience has been central to ongoing discussions about reconceptualizing the ICF (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantial impact that personal factors have on the lived experience of disability, there is wide debate regarding the identification of personal factors in rehabilitation literature (20,(23)(24)(25), and many factors identified as personal factors can actually be linked to other ICF levels (e.g., a body structure impairment is identified as a personal factor) (20). Nguyen et al (25) suggested that full implementation and translation of the ICF in rehabilitation is impeded by current lack of clarity about the specific impact of personal factors on disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation